Social Assistance for Poverty Reduction in the EU Countries: An Aspect of Socio-Economic Sustainability - Balvociute, Rasa (European Journal of Sustainable Development, 2020)
Research on the impact of social assistance benefits and other socio-economic indicators on poverty reduction during 2000 – 2017 in 24 EU countries is presented in the paper. In order to assess the impact a regression analysis model of the panel data was composed by including such indicators as changes in gross total expenditure per capita, the GDP growth rate, the share of the retirement-age population, the unemployment rate of the working-age population, the long-term unemployment rate. Research findings revealed the main socio-economic indicators that have the greatest impact on changes in poverty. The economic slowdown reduced the at-risk-of poverty gap of people with the lowest income and the economic growth reduced the poverty gap with a lag of two periods (years). The overall impact of all social transfers under analysis on the at-risk-of poverty gap was insignificant. The at-risk-of poverty rate, which shows changes in the share of the most deprived population under analysis, increased when non-targeted and means-tested benefits gal geriau social transfers increased. On the basis of these findings it can be stated that, during the period under analysis, social assistance was not well-directed, i.e. did not focus on the most deprived part of the population. Keywords: sustainable development, social assistance benefits, means-tested benefits, the at-risk-of-poverty rate, the relative poverty gap, panel data.